1998
DOI: 10.1148/radiology.207.3.9609890
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of mammographically detected clustered microcalcifications: is there any value?

Abstract: MR imaging of the breast is not reliable in differentiation of benign from malignant breast disease in mammographically suspicious clustered microcalcifications and has no effect on treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
2
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 0 publications
3
55
2
3
Order By: Relevance
“…Because DCIS is the earliest stage of breast cancer and has the best prognosis, it is likely that further improvements in the detection of breast cancers at a preinvasive stage may improve patient outcomes. Some reports have shown decreased diagnostic accuracy of DCE MR imaging for DCIS (2,3), while others have shown comparable or even higher performance compared with that of x-ray mammography (4,5). The sensitivity of DCE MR imaging for detection of DCIS may be compromised if the lesion does not exhibit sufficient gadolinium uptake or if it is obscured by strongly enhancing parenchyma (6,7).…”
Section: C3mentioning
confidence: 99%
“…Because DCIS is the earliest stage of breast cancer and has the best prognosis, it is likely that further improvements in the detection of breast cancers at a preinvasive stage may improve patient outcomes. Some reports have shown decreased diagnostic accuracy of DCE MR imaging for DCIS (2,3), while others have shown comparable or even higher performance compared with that of x-ray mammography (4,5). The sensitivity of DCE MR imaging for detection of DCIS may be compromised if the lesion does not exhibit sufficient gadolinium uptake or if it is obscured by strongly enhancing parenchyma (6,7).…”
Section: C3mentioning
confidence: 99%
“…Other MR studies have reported variable accuracy for classification of microcalcification. Westerhof et al (1998), investigating mammographically suspicious microcalcifications, reported a sensitivity of 45%, specificity of 72%, positive predictive value of 71%, negative predictive value 46% and an accuracy of 56%, and in a further study, Gilles et al observed a sensitivity of 95% and a specificity of 51%. Their specificity was impaired because the presence or absence of contrast uptake in the breast was the only parameter used to decide if the area of microcalcification was associated with malignancy or not (Gilles et al, 1996).…”
Section: Dcismentioning
confidence: 93%
“…Reports on the usefulness of MRI for the evaluation of calcified lesions began to appear in the late 1990s, but as the ability of MRI in the qualitative diagnosis of calcified lesions was insufficient, the benefit of MRI was refuted [142]. In the 2000s, the diagnostic ability of MRI was improved due to technical developments, and the recent changes in the clinical procedures associated with the introduction of SVAB have led to increases in reports recommending MRI [143][144][145].…”
Section: Commentsmentioning
confidence: 99%